2019
DOI: 10.3390/nano9121697
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Oxalate Ligand in Co-Precipitation Route on Morphological Properties and Phase Constitution of Undoped and Rh-Doped BaTiO3 Nanoparticles

Abstract: In order to design and tailor materials for a specific application like gas sensors, the synthesis route is of great importance. Undoped and rhodium-doped barium titanate powders were successfully synthesized by two routes; oxalate route and classic route (a modified conventional route where solid-state reactions and thermal evaporation induced precipitation takes place). Both powders were calcined at different temperatures. X-ray diffraction (XRD), Raman spectroscopy, scanning electron microscopy (SEM), energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…The materials we have prepared show stability on heating in air to only 600 • C, which demonstrates how it would be impossible to prepare the same samples by conventional solid-state synthesis, or even coprecipitation methods that require an annealing step. It is interesting to note that Rh 3+ -containing BaTiO 3 prepared by an oxalate-aided coprecipitation route showed extrusion of rhodium metal when heated above its synthesis temperature [30]. This illustrates the tendency for the precious metals to be reduced, but also how this may be aided by embedding in a host lattice by replacement of a cation of higher charge.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The materials we have prepared show stability on heating in air to only 600 • C, which demonstrates how it would be impossible to prepare the same samples by conventional solid-state synthesis, or even coprecipitation methods that require an annealing step. It is interesting to note that Rh 3+ -containing BaTiO 3 prepared by an oxalate-aided coprecipitation route showed extrusion of rhodium metal when heated above its synthesis temperature [30]. This illustrates the tendency for the precious metals to be reduced, but also how this may be aided by embedding in a host lattice by replacement of a cation of higher charge.…”
Section: Discussionmentioning
confidence: 89%
“…LaCr 1−x M x O 3 (LCMO) (x = 0.01, 0.05, 0.10 with M = Pd, Co, Ir) materials were prepared using conventional solid-state synthesis from single metal oxide precursors at 1200 • C, with a reduction in band gap observed for all substituted materials [29]. Rh-doped BaTiO 3 nanoparticles, with 2% of the substituent, were prepared by a co-precipitation route using oxalate as solution additive at temperatures between 700 and 900 • C [30]. The Rh was found in the +3 oxidation state and on heating to higher temperatures the rhodium was lost, with phase transformation of the perovskite.…”
Section: Introductionmentioning
confidence: 99%
“…The chelating‐agent assisted synthesis of BaTiO 3 was reported several decades ago and was, since then, largely reproduced, in particular with the aim of elaborating new multifunctional transition metal or rare‐earth doped BaTiO 3 nanocrystals that combine, for instance, SHG and up‐conversion emission properties. [ 151,152 ] However, if the synthesis method efficiently produces BaTiO 3 nanocrystals, the required thermal annealing inevitably induces particle aggregation. Among the oldest papers, one can mention the synthesis of cubic and tetragonal BaTiO 3 nanocrystals in the 50–300 nm size range that can be easily obtained after a thermal decomposition above 550°C of barium titanyl oxalate (BaTiO(C 2 O 4 ) 2 ·4H 2 O).…”
Section: Sol‐gel Methodsmentioning
confidence: 99%
“…As a consequence, the crystallization of BaTiO 3 is observed at 700 °C, leading to nanostructured, spherical but still aggregated nanopowders. [ 151 ] Very interestingly, a recent study demonstrates the importance of time‐resolved in situ infrared and XRD measurements to elucidate the formation mechanism of BaTiO 3 nanocrystals after drying at 150 °C of a mixture of Ti‐ and Ba‐solutions stabilized with citric acid and EDTA. If crystallization above 500 °C results from the reaction between two poorly crystallized, intermediate metastable phases (namely BaTi 4 O 9 and a calcite‐type BaCO 3 ), lowering the CO 2 partial pressure has been found key to avoid the formation of stable carbonates.…”
Section: Sol‐gel Methodsmentioning
confidence: 99%
“…Moving to the possibility of local stimulation at the affected area, this can be achieved by using piezoelectric, ferroelectric, or ferromagnetic materials that are distributed in a controlled manner and activated by the application of external electric or magnetic fields, subsequently improving the speed and quality of tissue regeneration by modifying the biological routes travelled by the cells [45]. One such example is barium titanate (BaTiO 3 ), which is a well-known ceramic with unique properties [16,[46][47][48][49]. It was demonstrated that the integration of hydroxyapatite and barium titanate powders in a collagen matrix can improve the osseointegration process of the resulting hybrid scaffolds [47], the influence of barium titanate being afterwards evaluated through numerical simulation [46].…”
Section: Introductionmentioning
confidence: 99%